Calcinosis in juvenile dermatomyositis: Updates on pathogenesis and treatment - Pinotti, Caitlan S.; Cannon, Laura; Dvergsten, Jeffrey A.; Wu, Eveline Y. (Frontiers in Medicine, 2023)
Calcinosis, or the deposition of insoluble calcium salts in the skin, subcutaneous tissue, fascia, tendons, and muscles, is a feared complication of juvenile dermatomyositis. Calcinosis is estimated to affect up to 40% of patients with juvenile dermatomyositis and contributes to significant disease morbidity. Calcinosis can be challenging to treat, and the most effective treatment remains unknown because of a lack of comparative studies. We aim to review the literature published in the last five years to summarize updates on the pathogenesis and treatment of calcinosis in juvenile dermatomyositis and describe future areas for research.